ANALISIS RISK PROFILE PADA PT. BANK NEGARA INDONESIA (PERSERO), TBK. PERIODE 2007-2011 DITINJAU DARI RISIKO LIKUIDITAS - DWI WULANDARI, SINDY Dwi (Jurnal Akuntansi AKUNESA, 2013)
This study aims to determine liquidity risk in BNI period 2007-2011, which refers to theattachment 13/24/DPNP Bank of Indonesia Number 25 October 2011. This research usesdescriptive quantitative method with secondary data from published financial statements PT BNITbk period 2007-2011. The results showed that channeling funds for operational activities inliquid assets BNI increased from year to year, but the rate of return of their funding ratiosrelative decline, so the magnitude of the risks must be borne by BNI on bad debt level (NPL) arealso getting bigger. However on the approach of total liabilities of commitment andcontigencies, BNI increased significantly, which indicates that the operational activities of theBNI increased.Keywords: Non Performing Loan, Liquidity, Liquidity Risk.